INTERNALISASI NILAI-NILAI PENDIDIKAN ISLAM PADA TRADISI MALAM SATU SURO - Kholivia Agustin Ningsih; Muliatul Maghfiroh (Pascasarjana Universitas Hindu Indonesia, 2024)
The combination of Islamic teachings and Javanese cultural behavior has become an interesting phenomenon for research. This is driven by the strength of the Javanese people in maintaining traditions. This research looks at the other side of this tradition, especially the suroan tradition in the people of Tambung Village, Pademawu District, Pamekasan Regency. The aim of this research is to determine the process of implementing the malam satu suro tradition and the values of Islamic education in the malam satu suro tradition in Tambung Village. The research method used is a qualitative method. The research subjects were taken from people who were directly involved and took an active part in following the malam satu suro tradition. The data collection techniques used were observation, interviews and documentation. The results of this research are the process of implementing the Malam Satu Suro tradition, namely: prayer beads, reading Qs. Yasin three times, dhikr together, torchlight parade, tadarus, and eating together. The values of Islamic education in the Malam Satu Suro tradition are the value of i'tiqodiyah education, the value of amaliyah education, and the value of khuluqiyah education.